Radical hysterectomy in early cervical cancer in Europe: characteristics, outcomes and evaluation of ESGO quality indicators. Issue 9 (September 2021) - Boria, Felix; Chiva, Luis; Zanagnolo, Vanna; Querleu, Denis; Martin-Calvo, Nerea; Căpîlna, Mihai Emil; Fagotti, Anna; Kucukmetin, Ali; Mom, Constantijne; Chakalova,, Galina; Shamistan, Aliyev; Malzoni, Mario; et al.
Abstract : Introduction: Comprehensive updated information on cervical cancer surgical treatment in Europe is scarce. Objective: To evaluate baseline characteristics of women with early cervical cancer and to analyze the outcomes of the ESGO quality indicators after radical hysterectomy in the SUCCOR database. Methods: The SUCCOR database consisted of 1272 patients who underwent radical hysterectomy for stage IB1 cervical cancer (FIGO 2009) between January 2013 and December 2014. After exclusion criteria, the final sample included 1156 patients. This study first described the clinical, surgical, pathological, and follow-up variables of this population and then analyzed the outcomes (disease-free survival and overall survival) after radical hysterectomy. Surgical-related ESGO quality indicators were assessed and the accomplishment of the stated recommendations was verified. Results: The mean age of the patients was 47.1 years (SD 10.8), with a mean body mass index of 25.4 kg/m 2 (SD 4.9). A total of 423 (36.6%) patients had a previous cone biopsy. Tumor size (clinical examination) <2 cm was observed in 667 (57.7%) patients. The most frequent histology type was squamous carcinoma (794 (68.7%) patients), and positive lymph nodes were found in 143 (12.4%) patients. A total of 633 (54.8%) patients were operated by open abdominal surgery. Intra-operative complications occurred in 108 (9.3%) patients, and post-operative complications during the first month occurred in 249 (21.5%) patients, with bladder dysfunction as the most frequent event (119 (10.3%) patients). Clavien-Dindo grade III or higher complication occurred in 56 (4.8%) patients. A total of 510 (44.1%) patients received adjuvant therapy. After a median follow-up of 58 months (range 0–84), the 5-year disease-free survival was 88.3%, and the overall survival was 94.9%. In our population, 10 of the 11 surgical-related quality indicators currently recommended by ESGO were fully fulfilled 5 years before its implementation. Conclusions: In this European cohort, the rate of adjuvant therapy after radical hysterectomy is higher than for most similar patients reported in the literature. The majority of centers were already following the European recommendations even 5 years prior to the ESGO quality indicator implementations.